Impact forces of granular flows on rigid structures: Comparison between discontinuous (DEM) and continuous (MPM) numerical approaches. (November 2018) - Ceccato, Francesca; Redaelli, Irene; di Prisco, Claudio; Simonini, Paolo
Abstract: The evaluation of forces due to the impact of flow-slides against structures is essential for both risk assessment and protection structure design. However, the impact process is very complex and not fully understood yet. Peak forces are in fact commonly evaluated by simplified empirical methods whose reliability is questionable. In this paper, the impact process is numerically investigated by comparing the results obtained from software based on a discontinuous Discrete Element Method (DEM) and a continuous Material Point Method (MPM). The impact process and its key features are highlighted and the principal parameters influencing the peak force value are identified. This study focuses on the impact phase, rather than on the propagation phase. The soil mass is initially positioned in front of the wall with a prescribed uniform velocity and the evolution of the impact force is monitored.